Evaluating responses to temperature during pre-metamorphosis and carry-over effects at post-metamorphosis in the wood tiger moth (Arctia plantaginis) - Galarza, Juan A. (Philos Trans R Soc Lond B Biol Sci, 2019)
Insect metamorphosis is one of the most recognized processes delimiting transitions between phenotypes. It has been traditionally postulated as an adaptive process decoupling traits between life stages, allowing evolutionary independence of pre- and post-metamorphic phenotypes. However, the degree of autonomy between these life stages varies depending on the species and has not been studied in detail over multiple traits simultaneously. Here, we reared full-sib larvae of the warningly coloured wood tiger moth (Arctia plantaginis) in different temperatures and examined their responses for phenotypic (melanization change, number of moults), gene expression (RNA-seq and qPCR of candidate genes for melanization and flight performance) and life-histories traits (pupal weight, and larval and pupal ages). In the emerging adults, we examined their phenotypes (melanization and size) and compared them at three condition proxies: heat absorption (ability to engage flight), flight metabolism (ability to sustain flight) and overall flight performance. We found that some larval responses, as evidenced by gene expression and change in melanization, did not have an effect on the adult (i.e. size and wing melanization), whereas other adult traits such as heat absorption, body melanization and flight performance were found to be impacted by rearing temperature. Adults reared at high temperature showed higher resting metabolic rate, lower body melanization, faster heating rate, lower body temperature at take-off and inferior flight performance than cold-reared adults. Thus, our results did not unambiguously support the environment-matching hypothesis. Our results illustrate the importance of assessing multiple traits across life stages as these may only be partly decoupled by metamorphosis. This article is part of the theme issue ‘The evolution of complete metamorphosis'.